Temporal and spatial changes of some nitrogen pollutants in the lower section of the Alkabeer Alshamali River - هيفا سوسن; أسعد عزيز; فارس رفاه (Latakia University Journal -Biological Sciences Series, 2022)
The Syrian Arab Republic suffers from a sever scarcity of water resources due to the its occurrence in the dry and half- dry region on the one hand and on the other hand the mismanagement of these water resources, and to exposure to pollutants resulting from various human activities (agricultural, industrial, and domestic). In this study, we are focusing on monitoring the changes in the concentrations of some nitrogen pollutants (nitrate and ammonium) which are one of the indicators of agricultural pollution. Samples were collected from the lower section of the Great Northern River. The studied indicators were PH, EC, nitrogen in its two main forms (nitrate, ammonium). The results showed a significant improvement in the quality of the river in terms of nitrate index, as nitrate concentrations decreased to below the internationally permissible limits. Whereas, the ammonium concentration showed significant pollution in sewage water, especially in the last section of the river, whereas the ammonium concentration were very high, reaching values that exceeded the internationally permissible limits.